Features of the inter-hemispheric field-aligned current system over Malaysia ionosphere - Abidin, Zamri Zainal; Jusoh, M.H.; Abbas, M.; Bolaji, O.S.; Yoshikawa, A. (Elsevier, 2019)
Magnetic records of the declination (D) component for the solar quiet year 2011–2013 obtained from Magnetic Data Acquisition System (MAGDAS) at Langkawi (Geog. Lon. 99.68∘ E, Geog. Lat. 6.30∘N), Malaysia were utilized in this study. The minutes averages were used to delineate the diurnal (Sq(D)) variation. The monthly mean (MSq(D)) and their seasonal variabilities (SVq(D)) were also analysed. The Sq(D) and their MSq(D) exhibit smooth regular occurring pattern in the month of April–September and became highly perturbed in October–March across the years. The highest positive (∼3.5 arc-min) and the negative (∼−3.0 arc-min) values were observed in August 2011 during the dawn and noon sectors. These maxima shifted to July and September in 2012 with peaks ∼3.2 and −3.0 arc-min. In 2013, the positive maximum (∼3.0 arc-min) and its negative (∼−2.5 arc-min) were again seen in August. This implies that the dawn and noon sectors of August 2011 and 2013 are strongly influenced by IHFACs and this effect shifted to July and September in 2012. IHFACs through the years flow from the winter to summer hemisphere during the noon and dusk sectors and flow in opposite direction during the dawn sector. The day-to-day magnitudes of Sq(D) and MSq(D) seems to suggest the inter-hemispheric imbalance of the ionospheric Sq current earlier established by Van Sabben as the cause of IHFACs is not strongly affected by the changes in annual solar variation. Dusk-side IHFACs were observed to be northbound in all the seasons with the exception of June solstice. The direction of IHFACs does not change except in April and November. The current intensity is not large in solstices except in August 2011 and 2013 but it shifted to July in 2012. The result further showed that the magnitude of the duskside IHFACS is determined to some extent by the strength of the noontime IHFACs. IHFACs were generally observed to be greater during the daytime than night-time hours. © 2018 Elsevier Ltd